2010
DOI: 10.1097/aln.0b013e3181de7107
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Hydrogen Sulfide Protects against Ventilator-induced Lung Injury

Abstract: Inhalation of hydrogen sulfide during mechanical ventilation protects against VILI by the inhibition of inflammatory and apoptotic responses. Hydrogen sulfide confers lung protection independently of its ability to induce mild hypothermia during ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 54 publications
11
110
1
1
Order By: Relevance
“…1 However, excessive alveolar distension can lead to lung injury due to increased pulmonary vascular permeability, alteration in lung mechanics, and increased production of inflammatory mediators. 2,3 Although modulation of ventilator settings such as applying low tidal volumes and low plateau pressure may help to relieve lung injury, 4 ventilator-induced lung injury (VILI) remains a major problem in the long-term use of mechanical ventilation with an unacceptably high rate of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, excessive alveolar distension can lead to lung injury due to increased pulmonary vascular permeability, alteration in lung mechanics, and increased production of inflammatory mediators. 2,3 Although modulation of ventilator settings such as applying low tidal volumes and low plateau pressure may help to relieve lung injury, 4 ventilator-induced lung injury (VILI) remains a major problem in the long-term use of mechanical ventilation with an unacceptably high rate of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining normothermia by external warming attenuated the metabolic depressor eff ect, but did not completely blunt the cardiovascular response [4]. Various other rodent models confi rmed these observations: Inhaling gaseous H 2 S [5]- [12] and infusing the soluble sulfi de salts, NaSH or Na 2 S [6], [13], [14], also induced a reversible reduction in energy expenditure with a [8], [13], ischemia/reperfusion [7], [9], [12], endotoxin challenge [11], or bacterial sepsis [14], this eff ect coincided with attenuation of lung [8], [12]- [14], liver [9], kidney [7] and heart [12] injury. Most importantly, survival was improved after otherwise lethal stress states, e. g., hemorrhagic shock [6] and exposure to hypoxic hypoxia (fraction of inspired O 2 [FiO 2 ] 5 %) [5].…”
Section: Rodent Modelsmentioning
confidence: 68%
“…Inhaling H 2 S prior to myocardial ischemia at concentrations that had no metabolic depressant eff ect (10 ppm) attenuated organ damage, but to a lesser degree than concentrations that reduced energy expenditure (100 ppm) [12], suggesting that hypometabolism may indeed enhance the organ-protective properties of H 2 S. Of note, in that study as well as in others demonstrating H 2 S-related organ production coinciding with reduced metabolic activity, hypothermia was prevented [5], [7], [9], [14], [15] in order to elucidate the impact of a simultaneous drop in core temperature. Moreover, organ protection and improved survival were also shown to be in part [12], [13], [15], [34], [35] or even completely [8], [11], [36], [37] independent of any H 2 Sinduced metabolic depression at all. Finally, data obtained in large animal (swine or sheep) models of shock resulting from ischemia/reperfusion [29], [38]- [42], hemorrhage and resuscitation [30], or burn injury [36] also suggested that the benefi cial eff ects of infusing Na 2 S were at least in part independent of metabolic depression and/or a fall in core temperature.…”
Section: Hypothermiamentioning
confidence: 99%
“…In addition, beneficial effects of H 2 S inhalation on lung injury have previously been found in another model of VILI. 3 Thereby, the question remains what the mechanism is of the observed toxicity of inhaled H 2 S in the present study.…”
mentioning
confidence: 75%